A citizen science approach to long‐term monitoring of humpback whales (Megaptera novaeangliae) off Sydney, Australia. Issue 2 (21st October 2019) - Pirotta, Vanessa; Reynolds, Wayne; Ross, Geoffrey; Jonsen, Ian; Grech, Alana; Slip, David; Harcourt, Robert
Abstract: The Cape Solander Whale Migration Study is a citizen science project that annually counts northward migrating humpback whales ( Megaptera novaeangliae ) off Cape Solander, Sydney, Australia. Dedicated observers have compiled a 20‐year data set (1997–2017) of shore‐based observations from Cape Solander's high vantage point. Using this long‐term data set collected by citizen scientists, we sought to estimate the humpback whale population trend as it continues to recover postexploitation. We estimated an exponential growth rate of 0.099 (95% CI = 0.079–0.119) using a generalized linear model, based on observer effort (number of observation days) and number of whales observed, equating to 10% per annum growth in sightings since 1997. We found that favorable weather conditions for spotting whales off Cape Solander consisted of winds <30 km/hr from a southerly through a north westerly direction. Incidental observations of other cetacean species included the endangered blue whale ( Balaenoptera musculus ) and data deficient species such as killer whales ( Orcinus orca ) and false killer whales ( Pseudorca crassidens ). Citizen science‐based studies can provide a cost‐effective approach to monitoring wildlife over the time necessary to detect change in a population. Information obtained from citizen science projects like this may help inform policy makers responsible for State and Federal protection of cetaceans in Australian waters and beyond.